Perdebatan Mengenai Hubungan Antara Agama dan Negara; Mengatasi Konflik Beragama Dalam Negara Berdasarkan Pemikiran Islam - Muhammad, Adji Suradji (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
Debating or discourse between state and religion will always interesting to be discussed consideringeach has a different footing. The state is a human concept while religion concept that comes from God.In any religion, including Islam, explicitly there is no necessity to form a state in the sense that as aWestern concept. After all this, religion does not forbid people to do ijtihat or attempt to establish theState to protect the rights of individuals formally and meet the needs of its people. Pluralism ordiversity that exist in the State of Indonesia both of ethnicity, language, religion and race has been achallenge to find the ideal pattern of relationship between state and church. Departing from the abovementioned conditions then formulated the problem, how the pattern of an ideal relationship betweenreligion and state efforts to what can be done to minimize potential conflicts arising from therelationship between the state with religion. From the discussion that has been done, then we concludethat pluralism is sunatullah so that humans could not meniadakanya. Therefore, the tolerance betweengroups into the keyword or keywords for mutual understanding and mutual understanding between thegroups. If there is a difference between one group against another, it is expected that a dialogicalcommunication can be done so that the differences become more enrich in creating order and harmonybetween groups.